2019
DOI: 10.22159/ajpcr.2019.v12i3.30875
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and Anti-Inflammatory Effects of Curcumin Contribute Into Attenuation of Acute Gentamicin-Induced Nephrotoxicity in Rats

Abstract: Objectives: Nephrotoxicity is a renal-specific situation in which the excretion of toxic metabolites is reduced due to toxic agents and drugs. Gentamicin is an antibiotic belongs to aminoglycoside group which may induce nephrotoxicity due to induction of oxidative stress. Curcumin is a component of traditional medicine with significant nephroprotective effect. Therefore, the objective of the present study was to evaluate the nephroprotective effect of curcumin on gentamicin-induced nephrotoxicity. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 14 publications
2
17
0
Order By: Relevance
“…Curcumin could reduce the biomarkers of renal injury and renal tubule necrosis in AKI. 46 Based on the data obtained from this study, the antioxidative effects of CUR play a significant role in its renoprotective properties against PolyE nephrotoxicity. Many clinical trials showed the protective effects of CUR in human diseases.…”
Section: Discussionmentioning
confidence: 79%
“…Curcumin could reduce the biomarkers of renal injury and renal tubule necrosis in AKI. 46 Based on the data obtained from this study, the antioxidative effects of CUR play a significant role in its renoprotective properties against PolyE nephrotoxicity. Many clinical trials showed the protective effects of CUR in human diseases.…”
Section: Discussionmentioning
confidence: 79%
“…SOX genes can regulate a number of developmental processes including lens, hair follicle, gut, B-cell, muscle, and blood vessel development [12].…”
Section: Discussionmentioning
confidence: 99%
“…Body mass index (BMI) equal to body weight in grams over the square of length in cm, BMI = BW (grams)/length (cm). [214]…”
Section: Methodsmentioning
confidence: 99%
“…Nephrotoxic drugs lead to acute injury of proximal renal tubules through activation of oxidative stress and interference with renal tubular transport processes. [2]…”
Section: Introductionmentioning
confidence: 99%